Clinical and Demographic Characteristics of Children With Hypertension - Flynn, Joseph; Zhang, Ying; Solar-Yohay, Susan; Shi, Victor (Hypertension (Dallas, Tex. 1979), 2012)
Most information describing hypertension in the young comes from single-center reports. To better understand contemporary demographic and clinical characteristics of hypertensive children and adolescents, we examined baseline data on 351 children aged 1 to <17 years old who were enrolled in 2 multicenter trials of valsartan. Anthropometric, laboratory, and demographic information at randomization was extracted from the clinical trials databases. Summary variables were created and compared for 3 age groups<6 years (n=90), 6 to <12 years (n=131), and 12 to <17 years (n=130). Comparisons were also made between different etiologies of hypertension and for different anthropometric categories. Children <6 years old were significantly more likely to have secondary hypertension and were significantly less likely to have weight or body mass index >95 percentile compared with older children. Estimated glomerular filtration rate was significantly lower in children <6 years old (90.9 ± 31.8 mL/min per 1.73 m) than in the other 2 age groups (6 to <12 years, 141.4 ± 42.1 mL/min per 1.73 m; 12 to <17 years, 138.3 ± 46.0 mL/min per 1.73 m). Frequency of total cholesterol >95 percentile was significantly lower in children aged <6 years. Diastolic blood pressure index (subject blood pressure÷95 percentile) was significantly higher in children <6 years old (1.1 versus 1.0 in both the 6 to <12 years and 12 to <17 years groups; both P<0.0001). We conclude that hypertensive children <6 years are more likely to have secondary hypertension and to have higher diastolic blood pressure and lower glomerular filtration rate and are less likely to be obese or to have elevated cholesterol than school-aged children or adolescents. These findings emphasize unique aspects of childhood hypertension that should be considered when evaluating children and adolescents with elevated blood pressure and in designing future clinical trials.